MONITORING PENURUNAN TANAH DI KOTA JAKARTA DAN SEKITARNYA BERDASAR DATA KONTINU GPS (CGPS) - Ridho Fadhilah, Alvin
Jakarta as the capital of the Republic of Indonesia has a role as the center of all activities of nation and state life in various fields. This makes the development in Jakarta continues to grow rapidly, even began to explore the area around Jakarta, such as Tangerang and Bekasi, and leaving the problem to the environment. One problem encountered is land subsidence. Causes of land subsidence include excessive ground water extraction, load building, the natural consolidation of the layers of soil, and influence of tectonic force. Data and information about land subsidence will be indispensable in various fields. The method can be used for monitoring land subsidence one of which is a geodetic method through Global Positioning System (GPS) survey. This study uses a continuous GPS (CGPS) already installed in the field, namely in North Jakarta (CJKT), South Tangerang (CTGR), and Bekasi (CBTU). Data processing was performed using the differential method with radial baseline to the reference point, i.e. BAKO point in Cibinong, Bogor. CGPS data processing results show that in North Jakarta occurred a land subsidence trend by 5.84 cm during 2012-2015, while the state of the ground surface in South Tangerang and Bekasi fairly stable with a downward trend in 2012-2016 by 1.55 cm. The results of the processing of the data are also compared with the data of the rainy and dry season, so that it can be known the effect of rain on land subsidence.